Pengaruh Harga, Kualitas Produk dan Diferensiasi Pelayanan terhadap Loyalitas Pelanggan yang Dimoderasi Variabel Kepuasan Pelanggan - Diah Cahyani (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study is to analyze: 1) the effect of price on customer satisfaction. 2) the effect of product quality on customer satisfaction. 3) the influence of service differentiation on customer satisfaction. 4) the effect of price on customer loyalty. 5) the effect of product quality on customer loyalty. 6) the influence of service differentiation on customer loyalty. 7) the influence of customer satisfaction on customer loyalty. 8) indirect effect of price on customer loyalty through customer satisfaction. 9) indirect effect of product quality on customer loyalty through customer satisfaction. 10) the indirect effect of service differentiation on customer loyalty through customer satisfaction. The number of subjects for UD. Sumber Roso customers is 840 customers/consumers. In sampling, the sample size is determined by the Slovin formula with a significance level of 0.01 so that the sample is determined to be 98 customers/consumers. In this research, the writer uses multiple linear regression analysis technique with SPSS program. V. 26.0. From the results of the analysis and discussion, it is concluded as follows: 1) price has no effect on customer satisfaction; 2) product quality has a significant effect on customer satisfaction; 3) service differentiation has a significant effect on customer satisfaction; 4) price has a significant effect on customer loyalty; 5) product quality has a significant effect on customer loyalty; 6) service differentiation has no effect on customer loyalty; 7) customer satisfaction has a significant effect on customer loyalty; 8) price has an indirect effect on customer loyalty through customer satisfaction as a moderating variable; 9) product quality has an indirect effect on customer loyalty through customer satisfaction as a moderating variable; 10) service differentiation has an indirect effect on customer loyalty through customer satisfaction as a moderating variable.